Molecular mechanism of Epimedium in the treatment of vascular dementia based on network pharmacology and molecular docking - Xie, Chenchen; Tang, Hao; Liu, Gang; Li, Changqing (Frontiers in Aging Neuroscience, 2022)
Backgroud: Vascular dementia is the second most common cause of dementia after Alzheimer's disease, accounting for an estimated 15% of cases. However, unlike Alzheimer's disease, there is no licensed treatment for vascular dementia. Recently, Epimedium has attracted great attention for its potential neuroprotective benefit. However, the direct role and mechanism of Epimedium on vascular dementia still lack systematic research. To systematically explore the possible pharmacological mechanism of Epimedium for the treatment of vascular dementia, network pharmacology analysis combined with a molecular docking technology was conducted. Methods: The bioactive compounds and targets of Epimedium were obtained from the TCMSP database. The potential targets of vascular dementia were identified from the DrugBank, OMIM, Genecards, Therapeutic Target Database, DisGeNET databases. GO and KEGG pathway analyses were performed. Molecular docking was applied to validate the interaction between active components and hub targets. Results: A total of 23 Epimedium active ingredients, and 71 intersecting targets of Epimedium against vascular dementia were obtained. The top 5 hub targets AKT1, TNF, IL1β, IL6 and MMP9 were identified, and molecular docking showed good binding. GO enrichment showed a total of 602 enrichment results, with 458 (80.56%) key targets mainly focused on biological processes (BP). The response to hypoxia, positive regulation of nitric oxide biosynthetic process, aging, inflammatory response, cellular response to lipopolysaccharide, negative regulation of apoptotic process were well ranked. KEGG pathway enrichment analysis identified the TNF signaling pathway as an important pathway, with the MAPK/extracellular signal-regulated kinase (ERK) and NF-κB signaling pathways as the key pathways involved. These pathways are closely related with oxidative stress, neuroinflammation, BBB dysfunction, apoptosis, demyelination and axonal damage during vascular dementia. Conclusion: Epimedium may exert a protective effect against vascular dementia through the alleviation of oxidative stress, neuroinflammation, BBB dysfunction, apoptosis, demyelination and axonal damage. This study explored the mechanism of Epimedium on vascular dementia systematically through a network pharmacological approach, which provides insight into the treatment of vascular dementia.